What clinical metabolomics will bring to the medicine of tomorrow - Le Gouellec, Audrey; Plazy, Caroline; Toussaint, Bertrand (Frontiers in Analytical Science, 2023)
The purpose of this review is to explore How clinical metabolomics could help physicians in the future. The recent advent of medical genomics brings new and interesting technological tools to measure genetic predispositions to a disease. But metabolomics will allow us to go even further in linking the patient's pathological phenotype with gene expression defects and metabolic disorders. It is in this context that the clinical chemist must adapt and be a force of proposal to meet these health challenges. He must help the clinician by mastering these new innovative tools, in order to participate in the implementation of clinical studies for the discovery of biomarkers, but also to propose the assays of biomarkers called "signatures", which can be composite biomarkers or fingerprints, which will ultimately guide the clinician. He will have to propose them as clinical chemistry tests. In the first part, we will look at some concrete examples of the use of clinical metabolomics in clinical research projects that have led to the identification of a new biomarker. We will use the example of, trimethylamine N-oxide (or TMAO), and review the clinical studies that have proposed TMAO as a biomarker for cardiovascular disease. In a second part, we will see through bibliographic studies, how the metabolomic fingerprint can be useful to build a supervised model for patient stratification. In conclusion, we will discuss the limitations currently open to debate.